2014 International Conference on Engineering, Technology and Innovation (ICE) 2014
DOI: 10.1109/ice.2014.6871565
|View full text |Cite
|
Sign up to set email alerts
|

A study for neutral format to exchange and reuse engineering knowledge in KBE applications

Abstract: In the discipline of Knowledge Based Engineering (KBE), we propose a study for a possible solution to reuse pieces of engineering knowledge that have been already represented in other software tools. Those tools are mainly programs or CAD files, and are usually stored in companies' repositories (databases and PLM systems among the others). For reusing, we mean the possibility of replicating tout-court a specific set of rules, geometry and user interfaces in different projects, software and even application fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Creating a KBE system is done in three steps: knowledge capturing, formalization, and representation (Colombo et al, 2014). In the knowledge capturing phase, information that supports the KBE system is collected by domain experts.…”
Section: Knowledge-based Engineeringmentioning
confidence: 99%
“…Creating a KBE system is done in three steps: knowledge capturing, formalization, and representation (Colombo et al, 2014). In the knowledge capturing phase, information that supports the KBE system is collected by domain experts.…”
Section: Knowledge-based Engineeringmentioning
confidence: 99%
“…This schema depicts a concept for representing in a neutral way a configured product definition, the explicit knowledge encapsulated in parameterized CAD models and the implicit knowledge related to the design intent and rationale of these models. In [4], the authors provide a study for a neutral format to exchange and reuse rule-based procedural knowledge across different KBE applications: the Rules Interchange Format (RIF). However, there is still a lack of standardized methods to extract and neutrally formalize knowledge from CAD and KBE models.…”
Section: Related Workmentioning
confidence: 99%
“…Manufacturing companies tend more and more to hoard engineering knowledge (the know-what, know-why and know-how of product designs) for partial or total reuse in different contexts and projects. However, identifying, extracting, storing, transmitting and reusing engineering knowledge is still an on-going challenge when heterogeneous applications are used [4]. This is mostly because engineering knowledge is embedded into CAD models and the know-how is locked down in the minds of domain experts, making it rather difficult to extract and reuse.…”
Section: Introductionmentioning
confidence: 99%
“…(define-activity-role :id <number>* :name <string> :successors <number>* :preconditions <PSL sentence>* :postconditions <PSL sentence>*) (Grüninger and Menzel, 2003) (define-object :name <KIF constant> :constraints <PSL sentence>*) (Grüninger and Menzel, 2003) (define-parameter :variable <KIF variable> :constraints <PSL sentence>*) (Grüninger and Menzel, 2003) Process-inputs, outputs, and parameters PSL, IDEF5, OWL-S, STEP Perakath et al, 1994;Knutilla et al, 1998;Grüninger and Cutting-Decelle, 2000;Pouchard et al, 2000;Pratt, 2001;Zha and Du, 2002;Grüninger and Menzel, 2003;Bock and Grüninger, 2004;Grüninger, 2004;Martin et al, 2004;Chen and Chen, 2005;Bechhofer, 2009;Grüninger, 2009;Lützenberger et al, 2012;W3C, 2012;Fellmann et al, 2013 Engineering rules, logic, constraints, rationale RuleML, RIF, OWL DL Boley et al, 2005;Bechhofer, 2009;Lützenberger et al, 2012;W3C, 2012;Fellmann et al, 2013;Colombo et al, 2014 Requirement Requirements interchange format (ReqIF), SysML requirements diagram Weilkiens, 2007;Lützenberger et al, 2012;Fellmann et al, 2013;OMG, 2013;Colombo et al, 2014 The object declaration can be a constant as shown in the first object declaration or a variable as shown in the next object declaration. The PSL syntax illustrating the flow of information along with extensions to illustrate parameters along with inputs and outputs is shown as follows, but only for blade geometry optimisation.…”
Section: Mapping Example: Manual Translation Of An Informal Process Tmentioning
confidence: 99%
“…RIF offers a major advantage as it can be expressed in both XML-based syntax and more importantly can be extended to AP242 of STEP (Lützenberger et al, 2012). It can integrate with any platform or a CAD/PDM platform (Colombo et al, 2014). RuleML is another format for representing and sharing of rules on the World Wide Web.…”
Section: Formal Modelling and Representation Techniquesmentioning
confidence: 99%